Insecticide-Treated Net Campaign and Malaria Transmission in Western Kenya: 2003–2015 - Zhou, Guofa; Lee, Ming-Chieh; Githeko, Andrew K.; Atieli, Harrysone E.; Yan, Guiyun (Frontiers in Public Health, 2016)
Insecticide-treated nets (ITNs) are among the three major intervention measures that have reduced malaria transmission in the past decade. However, increased insecticide resistance in vectors, together with outdoor transmission, has limited the efficacy of the ITN scaling-up efforts. Observations on longitudinal changes in ITN coverage and its impact on malaria transmission allow policy makers to make informed adjustments to control strategies. We analyzed field surveys on ITN ownership, malaria parasite prevalence, and malaria vector population dynamics in seven sentinel sites in western Kenya from 2003 to 2015. We found that ITN ownership has increased from an average of 18% in 2003 to 85% in 2015. Malaria parasite prevalence in school children decreased by about 70% from 2003 to 2008 (the first mass distribution of free ITNs was in 2006) but has resurged by >50% since then. At the community level, use of ITNs reduced infections by 23% in 2008 and 43% in 2010, although the reduction was down to 25% in 2011. The indoor-resting density of the predominant vector, Anopheles gambiae, has been suppressed since 2007; however, Anopheles funestus populations have resurged and have increased 20-fold in some places since 2007. In conclusion, there is limited room for further increase in ITN coverage in western Kenya. The rebounding in malaria transmission highlights the urgent need of new or improved malaria control interventions so as to further reduce malaria transmission.